Digital Laser Micropainting for Reprogrammable Optoelectronic Applications. (28th September 2020) - Lee, Younggeun; Kwon, Jinhyeong; Lim, Jaemook; Shin, Wooseop; Park, Sewoong; Hwang, Eunseung; Shin, Jaeho; Cho, Hyunmin; Jung, Jinwook; Kim, Hyun‐Jong; Han, Seungyong; Lee, Habeom; et al.
Abstract: Structural coloration is closely related to the progress of innovative optoelectronic applications, but the absence of direct, on‐demand, and rewritable coloration schemes has impeded advances in the relevant area, particularly including the development of customized, reprogrammable optoelectronic devices. To overcome these limitations, a digital laser micropainting technique, based on controlled thin‐film interference, is proposed through direct growth of the absorbing metal oxide layer on a metallic reflector in the solution environment via a laser. A continuous‐wave laser simultaneously performs two functions—a photothermal reaction for site‐selective metal oxide layer growth and in situ real‐time monitoring of its thickness—while the reflection spectrum is tuned in a broad visible spectrum according to the laser fluence. The scalability and controllability of the proposed scheme is verified by laser‐printed painting, while altering the thickness via supplementary irradiation of the identical laser in the homogeneous and heterogeneous solutions facilitates the modification of the original coloration. Finally, the proof‐of‐concept bolometer device verifies that specific wavelength‐dependent photoresponsivity can be assigned, erased, and reassigned by the successive application of the proposed digital laser micropainting technique, which substantiates its potential to offer a new route for reprogrammable optoelectronic applications. Abstract : A digital laser micropainting technique, based on controlled thin‐film interference, is proposed through direct laser growth of the absorbing metal oxide layer on a metallic reflector. Specific wavelength‐dependent photoresponsivity can be assigned, erased, and reassigned to an optoelectronic device by the successive application of the proposed technique, which substantiates its potential for future reprogrammable optoelectronic applications.